Application of genetic technology in support of the northern hard clam (Mercenaria mercenaria) aquaculture industry - McCarty, Alexandra J.; McDowell, Jan R.; Reece, Kimberly S.; Snyder, Richard A.; Hudson, Karen (Frontiers in Aquaculture, 2025)
IntroductionThe northern quahog (hard clam, Mercenaria mercenaria) aquaculture industry on the Eastern Shore of Virginia produces the top seafood item by value in the Commonwealth of Virginia and is the largest hard clam aquaculture industry in the United States. This work resulted from industry interest in using molecular tools to assess and manage the genetic health of their proprietary broodstock lines.MethodsTo demonstrate the application of molecular methods, scientists and extension specialists genotyped hard clam samples from three commercial companies in Virginia, compared the results with previous work documenting the genetic structure of wild populations along the East Coast of North America, and compiled a toolbox of genetic tests appropriate for industry use.ResultsPrincipal component analysis, pairwise FST values, and Discriminant Analysis of Principal Components (DAPC) indicated that each group of cultured hard clam samples were significantly different from the wild populations and from each other. However, observed and expected heterozygosity, inbreeding values, and relatedness were similar between the wild populations and cultured stocks. These results have encouraged industry to monitor the genetic features of their broodstock to prevent the loss of genetic diversity and unintentional inbreeding.DiscussionThis project was successful in providing information on the genetic health (diversity and inbreeding) of Virginia hard clam cultured stocks, communicating the utility of genetic tools available for assessing and managing broodstock lines, and providing the hard clam industry with pathways to access additional genetic information in support of industry resilience.